2011
DOI: 10.1007/s10195-011-0136-0
|View full text |Cite
|
Sign up to set email alerts
|

Perforator-based propeller flaps treating loss of substance in the lower limb

Abstract: BackgroundLocal flaps based on perforator vessels are raising interest in reconstructive surgery of the limbs. These flaps allow efficient coverage of large wounds without the need to sacrifice a major vascular axis. The operative technique does not require microvascular anastomosis and allows reconstruction of soft tissue defects using nearby similar tissues. The aim of this study was to evaluate the clinical results of local perforator flaps in the treatment of complex lower-limb defects.Materials and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 19 publications
(21 reference statements)
1
36
2
1
Order By: Relevance
“…The reconstruction technique of the lower limb should ideally replace like-to-like tissue, minimize donor-site morbidity, preserve main vascular trunks, and reduce operating and hospitalization time [12]. The development of propeller flaps in reconstructive microsurgery has been facilitated by improved knowledge of the arterial basis of flap perfusion and anatomical studies on lower limb vascularization provided the basis for local perforator flap design [13].…”
Section: Discussionmentioning
confidence: 99%
“…The reconstruction technique of the lower limb should ideally replace like-to-like tissue, minimize donor-site morbidity, preserve main vascular trunks, and reduce operating and hospitalization time [12]. The development of propeller flaps in reconstructive microsurgery has been facilitated by improved knowledge of the arterial basis of flap perfusion and anatomical studies on lower limb vascularization provided the basis for local perforator flap design [13].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, many authors reported clinical series using propeller flaps for the reconstruction of the lower limb [11, 2426]. …”
Section: Discussionmentioning
confidence: 99%
“…Venous drainage of the angiosome typically occurs through the greater saphenous vein, which has numerous valves that prevent retrograde drainage of the distally based flap (16)(17)(18). However, when harvesting a reverse flap, the reflow blood will still conform to its original direction through the greater saphenous vein; thus, we have routinely sutured the distal end of the greater saphenous vein to facilitate drainage of the flap through the proximal end.…”
Section: Discussionmentioning
confidence: 98%
“…In general, the most prevalent complication associated with perforator flap tissue transfer has been complete or partial flap loss owing to venous congestion (16,17). Venous drainage of the angiosome typically occurs through the greater saphenous vein, which has numerous valves that prevent retrograde drainage of the distally based flap (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%